Implementasi Fuzzy Logic dalam Pembuatan Kontrol Navigasi Mobile Robot - Dairoh, Dairoh; Khambali, Mohammad; Mustofa, Trima (Lambung Mangkurat University Press, 2019)
Artificial Intelligence is defined as intelligence exhibited by an artificial entity. Intelligence was created and put into a machine that can do the job as do humans. Some kinds of fields that use artificial intelligence include fuzzy logic, expert systems, computer games, neural networks and robotics. The purpose of research is Applying the theory of fuzzy logic in the manufacture of robot control and create teaching materials for the subjects of physics, especially on the concept of a microcontroller or other allied subjects of the research conducted. In this study apply fuzzy logic on the movement of wheeled robot control where in the controlling controlled via a smartphone which is then processed by a microcontroller Arduino that has grown the program by applying the method of fuzzy logic rule. Then by the microcontroller is used as a command to drive the DC motor as a navigation system that course in accordance with the rules created. Every step of the control system provides a signal in the form of a large steering angle (Î¸) which guides the robot to the target of a starting position. The results showed that the application of a system of fuzzy logic can be implemented in a navigation system for a robot control and the results of testing the robot's movement, then obtained some data points specified coordinates with the coordinates of the control robot acquired a 96% accuracy rate.